2020
DOI: 10.1177/1010539520911493
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Ecological Theory to Identify Factors Associated With Risky Sexual Behavior in Cambodian Adolescent Girls and Young Women Aged 10 to 24 Years: A Systematic Review

Abstract: There is an increase in risky sexual behavior (RSB) in Cambodian female youth aged 10 to 24 years, which can contribute to detrimental sexual and reproductive health due to the increased risk of acquiring sexually transmitted infections, unintended pregnancies, or abortions. Bronfenbrenner’s social ecological model was used to identify factors at personal, microenvironment, and macroenvironment levels potentially associated with RSB. A systematic literature review employing PRISMA (Preferred Reporting Items fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Unmet need for contraception in females in Cambodia and other low-to-middle-income countries (LMICs) is associated with sexually transmitted infections (STIs), unintended pregnancies and unsafe abortions as a result of risky sexual behavior or unsafe sex which contribute to maternal morbidity and mortality (Hegde, Hoban & Nevill, 2012;Rizvi et al, 2020;Sedgh, Ashford & Hussain, 2016b). Bradley et al (2012) proposed a revised algorithm to calculate unmet need for the Demographic Health Surveys (DHS) including a complex measurement of 15 survey items (USAID, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmet need for contraception in females in Cambodia and other low-to-middle-income countries (LMICs) is associated with sexually transmitted infections (STIs), unintended pregnancies and unsafe abortions as a result of risky sexual behavior or unsafe sex which contribute to maternal morbidity and mortality (Hegde, Hoban & Nevill, 2012;Rizvi et al, 2020;Sedgh, Ashford & Hussain, 2016b). Bradley et al (2012) proposed a revised algorithm to calculate unmet need for the Demographic Health Surveys (DHS) including a complex measurement of 15 survey items (USAID, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Gender inequality is one of the challenges to sustainable development in most LMICs in East-Asia and South-East Asia, including Cambodia, Myanmar, Lao PDR, Timor-Leste, Indonesia, Vietnam and the Philippines ( UNICEF, 2019 ). The disproportionate burden of SRH issues and high unmet need in female adolescents and young people in Cambodia and other LMICs in the Asia-Pacific region is often made worse by lack of health literacy, and non-existent SRH services ( Chandra-Mouli et al, 2019 ; Rizvi et al, 2020 ; Sedgh, Ashford & Hussain, 2016a ). There is strong research evidence for integrated SRH literacy and family planning services, and increased number of schools with improved education and targeted interventions to reduce school dropouts especially for female adolescents ( Azzopardi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We posit that the young females usually reside in the low socioeconomic, peri-urban areas with limited access to SRH and family planning services. Additionally, a review of literature from Cambodia showed increased rural to urban migration with many female youth finding employment in the entertainment industries [11,33]. These female youth face multiple barriers in accessing SRH services including personal, financial, literacy or information, communication, and cultural barriers [11,33].…”
Section: Discussionmentioning
confidence: 99%
“…Our study's focus is on Cambodian sexually active female adolescents and women aged 15-29 years as the negative repercussions of unsafe sex, and high unmet need for modern contraception in females are serious in terms of the risk of having sexually transmitted infections (STIs), unintended pregnancies or induced abortions [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Past systematic reviews have focussed on treatment effects and scale of sexual aggression and protective factors but none on psychosocial determinants or factors that contribute to sexual deviance of adolescents speci cally [2][3][13][14][15]. This current systematic review intends to elucidates the occurrence of sexual deviance amongst ASEAN adolescents and the psychosocial antecedents that contribute to their intent of deviance through value as source of attitude.…”
Section: Introductionmentioning
confidence: 99%